A Novel lncRNA IHS Promotes Tumor Proliferation and Metastasis in HCC by Regulating the ERK- and AKT/GSK-3β-Signaling Pathways - Chen, Zheng (Mol Ther Nucleic Acids, 2019)
Long noncoding RNAs (lncRNAs) are involved in a variety of biological processes such as tumor proliferation and metastasis. A close relationship between hepatitis B virus X protein (HBx) and SMYD3 in promoting the proliferation and metastasis of hepatocellular carcinoma (HCC) was recently reported. However, the exact oncogenic mechanism of HBx-SMYD3 remains unknown. In this study, by performing lncRNA microarray analysis, we identified a novel lncRNA that was regulated by both HBx and SMYD3, and we named it lncIHS (lncRNA intersection between HBx microarray and SMYD3 microarray). lncIHS was overexpressed in HCC and decreased the survival rate of HCC patients. Knockdown of lncIHS inhibited HCC cell migration, invasion, and proliferation, and vice versa. Further study showed that lncIHS positively regulated the expression of epithelial mesenchymal transition (EMT)-related markers c-Myc and Cyclin D1, as well as the activation of the ERK- and AKT-signaling pathways. lncIHS exerted its oncogenic effect through ERK and AKT signaling. Moreover, results from transcriptome-sequencing analysis and mass spectrometry showed that lncIHS regulated multiple genes that were the upstream molecules of the ERK- and AKT-signaling pathways. Therefore, our findings suggest a regulatory network of ERK and AKT signaling through lncIHS, which is downstream of HBx-SMYD3, and they indicate that lncIHS may be a potential target for treating HCC.